Kierkegaard and the Refusal of Transcendence - Shakespeare, Steven. author. aut Link
XV, 236 p.
Keywords: Kierkegaard and the Refusal of Transcendence challenges the standard view that Kierkegaard's God is infinitely other than the world. It argues that his work immerses us in the paradoxical nature of existence itself, and opposes any flight into another world.